Forests and French sea power, 1660-1789 - Bamford, Paul W. (Paul Walden), 1921- (University of Toronto Press, 1956)
By choosing to concentrate upon discovering what forest resources were available to the French navy during the ancien régime and what use it was able to make of them, Mr. Bamford has not only provided the first monograph on that subject in the English language, but has gone far toward explaining why France was the loser in the long duel with England for the control of commerce and the extension of empire. Two years of research in the Archives Nationales and in the Archives de la Marine in Paris, Toulon, and Rochefort enabled him to draw on contemporary sources of information of which little, if any, use has been made before, and a further year of research in the libraries of New York City, particularly in the rich Proudfit Naval Collection, also yielded new material. It is Mr. Bamford's achievement to have handled this vast store of primary sources with such skill and judgement that the reader, by turning over letters from disgruntled forest proprietors, reports from harassed maîtres on the trickery and recalcitrance of the peasants, instructions from the top echelon of the navy to inspectors in the forests, and a variety bills, receipts, and memoranda, is given at first hand an appreciation of the difficulties faced by the navy in trying to obtain timber and masts of the choice quality required for building ships-of-the-line. The navy had to compete with the merchant marine and with industrial and private users of fuel for supplies that were continually being depleted by mismanagement and by the conversion of forests to arable land. Measures, superficially admirable, for conserving the forests are found on closer examination to be at once over-precise and not properly enforced. Transport, even in a country so abundantly supplied with navigable rivers as France, was expensive and difficult.
Keywords: France. -- Marine -- Supplies and stores.; France. -- Marine -- History.; France. -- Marine -- Histoire.; France. -- Marine -- Matériel.; France. -- Marine; France -- History, Naval -- 17th century.; France -- History, Naval -- 18th century.; Timber.; Forests and forestry -- France.; Wood.; Wood; Bois.; France -- Histoire navale -- 17e siècle.; France -- Histoire navale -- 18e siècle.; Bois d'œuvre.; wood (plant material); timber logs.; HISTORY -- Military -- Naval.; TECHNOLOGY & ENGINEERING -- Marine & Naval.; TECHNOLOGY & ENGINEERING -- Military Science.; Forests and forestry; Military supplies; Timber; France; 1600-1799; Naval history